Cloning and expression of influenza A virus protiens and its use in serological assay - Norkasinah, Binti Ramji (Universiti Malaysia Sarawak (UNIMAS), 2009)
Avian influenza poses a threat to many species including human, as proven by the current situation in Southeast Asia region. It appears that avian influenza of influenza A virus can spread to many species causing severe disease in these new species. The aim of this study is to clone and expressed the major influenza A virus proteins namely matrix 1 (M1), matrix 2 (M2), hemagglutinin 1 (HA1), hemagglutinin 2 (HA2) and nucleoprotein (NP) and also to assess its use in serological assay. Although all genes studied were successfully cloned, only the M1 construct protein resulted in good protein expression. The matrix 1 protein is a conserved protein. The viral gene encoding matrix protein 1 (M1) of influenza A virus is a multifunctional protein that plays essential structural and function roles in virus life cycle. M1 forms the major structural component of the virion, lying beneath the lipid envelope containing the viral hemaglutinin (HA) and neuraminidase (NA) glycoproteins and the M2 ion channel and it is presumed to play an important factor in initiating progeny virus assembly